The Influence of Digital Leadership Toward Digital Transformation of Education - Suratman, Suratman; Torres, Joel Mayo; Salehudin, Mohammad; Susmiyati, Sri; Sugiyono, Sugiyono (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Digital leadership faces challenges in transformation, including inadequate internet access, limited funding, and low teacher digital competence. Moreover, institutions struggle to maintain learning quality and safeguard digital privacy. Organizational culture remains unprepared for digitalization, with insufficient strategies to adapt to change. These issues create anxiety among principals and teachers in integrating technology, while a lack of understanding of digital leadership within institutions hinders innovation and performance improvement. This study aimed to analyze the effect of digital leadership on educational digital transformation using a quantitative approach. The population consisted of all school principals and teachers at Madrasah Aliyah in Samarinda, totaling 120 individuals. The sampling technique employed the Harry King Nomogram table with a 5% margin of error, resulting in a sample size of 92 participants. Data were collected through questionnaires and analyzed using linear correlation and t-tests. The results showed that digital leadership significantly impacts digital transformation, enhancing infrastructure, training, digital content, student engagement, creativity, and performance measurement. Digital transformation in education is achieved through integrating technology into learning processes and improving school management efficiency. This underscores the critical role of digital leadership in addressing technological challenges and fostering innovation in educational institutions.